2020
DOI: 10.1371/journal.pone.0229533
|View full text |Cite
|
Sign up to set email alerts
|

Seizing opportunities for intervention: Changing HIV-related knowledge among men who have sex with men and transgender women attending trusted community centers in Nigeria

Abstract: Background Knowledge of HIV risk factors and reduction strategies is essential for prevention in key populations such as men who have sex with men (MSM) and transgender women (TGW). We evaluated factors associated with HIV-related knowledge among MSM and TGW and the impact of engagement in care at trusted community health centers in Nigeria. Methods The TRUST/RV368 cohort recruited MSM and TGW in Lagos and Abuja, Nigeria via respondent driven sampling. During study visits every three months, participants under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Thus, behavioral change intervention strategies that favor PLHIV should be encouraged. Governmental policy and laws should be modified to be more accommodating to all groups, as policies that segregate a particular group may hamper on the progress of HIV interventions and programs [ 53 ]. With Nigeria a signatory to numerous of human rights declarations including the Convention on Elimination of all Form of Stigma and Discrimination against Women [ 54 ]; there is the need for human rights organizations to intensify efforts in the enforcement of the anti-HIV discrimination law and ensure the conformity to these rights, with more innovative efforts towards HIV/AIDS advocacy, awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, behavioral change intervention strategies that favor PLHIV should be encouraged. Governmental policy and laws should be modified to be more accommodating to all groups, as policies that segregate a particular group may hamper on the progress of HIV interventions and programs [ 53 ]. With Nigeria a signatory to numerous of human rights declarations including the Convention on Elimination of all Form of Stigma and Discrimination against Women [ 54 ]; there is the need for human rights organizations to intensify efforts in the enforcement of the anti-HIV discrimination law and ensure the conformity to these rights, with more innovative efforts towards HIV/AIDS advocacy, awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Together, facilities focused on the social, legal and sexual health needs of study participants and sensitization training was provided to promote integration of the two entities. Services included education about safer sex practices, distribution of condoms and condom‐compatible lubricants and diagnosis and treatment of HIV and other sexually transmitted infections (STIs) [14‐19]. Despite these services, we have previously reported a high HIV incidence of 15 infections per 100 person‐years in the cohort [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is in keeping with previous work by our group, which demonstrated that ongoing care engagement at a trusted community clinic resulted in improvements over time in other health-related outcome measures such as increased HIV knowledge, condom use, and condom-compatible lubricant use. 46,47 Unmeasured biases may have contributed to these outcomes and alternative explanations are possible. For example, who had the most food and water security could be more likely to remain in this study; however, several observed factors associated with water insecurity were robust to sensitivity analysis limited to participants who were followed through the end of this study.…”
Section: Discussionmentioning
confidence: 99%